Matematyka
wenus24
2017-12-30 18:46:19
Matematyka , rozłóż wyrażenia na czynniki Chodzi mi o rozpisania przykładów c,f,i
Odpowiedź
grazynka1069
2017-12-30 19:22:12

[latex]x^{3}-4x^{2}+4x=x(x^{2}-4x+4)=x(x^{2}-2*x*2+2^{2})=x(x-2)^{2}\ \ 8yx^{2}-8yx+2y=2y(4x^{2}-4x+1)=2y((2x)^{2}-2*2x*1+1^{2})=\ =2y(2x-1)^{2}\ \ 27x^{3}+18x^{2}+3x=3x(9x^{2}+6x+1)=2x((3x)^{2}+2*3x*1+1^{2})=\ =2x(3x+1)^{2}[/latex]

blackmagix1
2017-12-30 19:23:27

[latex]c) \ x^3-4x^2+4x=x(x^2-4x+4)=x(x-2)^2 \ \ f) \ 8yx^2-8yx+2y=2y(4x^2-4x+1)=2y*4(x- frac{1}{2})^2=8y(x- frac{1}{2})^2 \ \ i) \ 27x^3+18x^2+3x=3x(9x^2+6x+1)=3x*9(x+ frac{1}{3})^2=27x(x+ frac{1}{3})^2 [/latex]

Dodaj swoją odpowiedź